Engaged Learning-Transversal Legacies in Didactics of Social Sciences in English - Lechuga Jiménez, Clotilde; Griffith, Mary (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This study makes Engaged Learning visible in Primary Education classrooms with content in English, taking into account the Cultural Heritage of the students’ environment, according to UNESCO. It promotes the Transversal Legacy in Didactics of Social Sciences with the use of Visual Research Methodologies (VRM) and interviews with elders and people close to them, in order to explore and finally analyse existing needs in the community or close environment. The aim is to involve the University in social issues -localising and seeking solutions- giving a voice to students and citizens, with an emphasis on internationalisation and identity legacies.